Menelaah Kontribusi Serikat Pekerja dalam Menjamin Hak Karyawan Melalui Perjanjian Kerja Berdasarkan Hukum Ketenagakerjaan Indonesia - Fatmawati, Fitri; Hari, Hari; Ilham, Ilham; Jaenudin, Muhamad (AGUSPATI RESEARCH INSTITUTA, 2025)
Labor organizations, commonly known as trade unions, are essentially the primary tool for workers to protect and fight for the normative rights of employes within a company. As regulated by the government in Law No. 21/2000 concerning trade unions; this is a regulation that specifically governs the maximum implementation and function of trade unions, which are open, free, democratic, and responsible for fighting for, defending, and protecting the rights and obligations of their members (workers/laborers). Therefore, the presence of trade unions becomes important as a party that can fight for and guaranty the fulfillment of employe rights. This research aims to examine the contribution of trade unions in ensuring employe rights thru employment agreements based on labor law.